Teatro como “acontecimiento” en la América Latina de los años 50 y 60 - Muguercia, Magaly (Latin American Theatre Review, 2014)
On the threshold of the “revolutionary years,” Latin American artists began to think of theatricality in terms of an “event,” as the emergence of the new on a physical level, beyond ideology and questions of representation. This article presents examples of this trend in anthropologically-inspired works performed during the 1950s, outside conventional theatre spaces. Experiments with theatre-in-the round produce effects on the audience that correspond neither to identification nor to “alienation.” Latin American “happenings” and the practices of groups such as Arena and Opinião in Brazil raise questions regarding the relationship between theatre and politics, as groups move away from principles of representation in order to focus on theatre as a radical “event” based on extreme corporality.